DOES PREOPERATIVE COUNSELLING HELP IMPROVE PATIENTS’ SATISFACTION WITH PAIN MANAGEMENT IN POSTOPERATIVE PERIOD - JAMIL, H; ZAHID, R; WAHEED, H; ASLAM, A; KHUWAJA, S (Biological and Clinical Sciences Research Journal, 2024)
Postoperative pain management is a critical aspect of care in the postoperative unit. While various analgesic drugs are commonly used, the role of preoperative counseling regarding the procedure and its potential outcomes is gaining recognition for its importance. However, there is limited research exploring this aspect. Objective: To compare the mean pain scores after preoperative counseling versus no counseling in patients undergoing elective surgery. Methods: This randomized controlled trial was conducted in the Department of Anaesthesiology, Hameed Latif Hospital, Lahore, from 15th May 2019 to 15th November 2019. Sixty patients aged 20-50, of either gender, undergoing general surgery under general anesthesia with ASA class I/II, were included. Patients were divided into two groups: those who received preoperative counseling (group A) and those who did not (group B). Preoperative counseling included information on the type of surgery, duration, possible complications, degree of pain, and its management. Postoperative pain was assessed using the Visual Analogue Scale (VAS) 6 hours after surgery. Statistical analysis was performed to compare the mean pain scores between the two groups. Results: The study included 60 patients, 19 males in group A and 20 in group B. The mean age was 36.47±8.32 years in group A and 36.93±8.83 years in group B (p=0.79). The mean postoperative pain score on VAS was 3.43±1.07 in the group that received preoperative counseling (group A) and 5.03±1.61 in the group without counseling (group B) (p=0.03). Pain scores in males were 3.31±0.83 in group A and 4.97±1.47 in group B (p=0.01). In females, scores were 3.49±0.97 in group A and 5.53±1.73 in group B (p=0.03). In the 20-34 age group, the pain score was 3.38±0.97 in group A and 4.99±1.21 in group B (p=0.02), and in the 35-50 age group, the score was 3.44±1.05 in group A and 5.05±1.29 in group B (p=0.03). VAS scores were 3.46±1.07 in ASA class I and 3.27±0.95 in ASA class II in group A, compared to 5.03±1.63 and 5.03±1.45 in group B, respectively (p=0.03 each). Pain scores were also significantly better in group A across different educational statuses. Conclusion: Preoperative counseling substantially reduces postoperative pain scores as measured by the Visual Analogue Scale, compared to no counseling. This difference is statistically significant across various demographic and clinical subgroups.